2008
DOI: 10.1016/j.devcel.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Inhibition of JAK/STAT Signaling by Apontic Is Required to Limit an Invasive Cell Population

Abstract: In both normal development and in a variety of pathological conditions, epithelial cells can acquire migratory and invasive properties. Border cells in the Drosophila ovary provide a genetically tractable model for elucidating the mechanisms controlling such behaviors. Here we report the identification of a mutant, apontic (apt), in which the migratory population expanded and separation from the epithelium was impeded. This phenotype resembled gain-of-function of JAK/STAT activity. Gain-of-function of APT also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
137
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(146 citation statements)
references
References 40 publications
9
137
0
Order By: Relevance
“…1G,J,K) suggests that JAK/STAT signalling might be affected. To further investigate the role of MT or Dynein in oBC specification through JAK/STAT signalling we used the 10ϫSTAT92EGFP reporter line, which accurately reflects JAK/STAT activity (Bach et al, 2007;Starz-Gaiano et al, 2008). At stage 8, GFP accumulates in the nuclei of follicular cells surrounding the PCs in a graded manner.…”
Section: Jak/stat Signalling Is Altered In the Absence Of Dynein Cargmentioning
confidence: 99%
See 2 more Smart Citations
“…1G,J,K) suggests that JAK/STAT signalling might be affected. To further investigate the role of MT or Dynein in oBC specification through JAK/STAT signalling we used the 10ϫSTAT92EGFP reporter line, which accurately reflects JAK/STAT activity (Bach et al, 2007;Starz-Gaiano et al, 2008). At stage 8, GFP accumulates in the nuclei of follicular cells surrounding the PCs in a graded manner.…”
Section: Jak/stat Signalling Is Altered In the Absence Of Dynein Cargmentioning
confidence: 99%
“…The transport of upd mRNA and the subsequent accumulation of the Upd protein apically contribute to setting the high concentration of ligand required for oBC determination. Recently, a new negative-feedback mechanism has been identified in oBCs that involves a regulatory circuit between Slbo, STAT and Apt (Starz-Gaiano et al, 2008;Starz-Gaiano et al, 2009). This feedback mechanism inhibits JAK/STAT activity in cells that receive low levels of Upd ligand, i.e.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a number of studies have reported other genes in which mutant clones were observed to lag behind the cluster, causing a delay in migration (Rorth et al, 2000;Bianco et al, 2007;Starz-Gaiano et al, 2008). In this study, we provide the first example of acceleration of clusters caused by sima or tgo mutations in a single leading cell.…”
Section: Discussionmentioning
confidence: 75%
“…Reduction of Stat92E activity during the migration process (Silver et al, 2005), as well as its overactivation, interferes with BCC migration (Yoon et al, 2011). Loss of slbo function in rosette cells blocks the motility of the BCC (Montell et al, 1992;Rørth et al, 2000), whereas overexpression of slbo causes a delay in migration and frequently a fragmentation of the BCC (Rørth et al, 2000;Starz-Gaiano et al, 2008). Similarly, not only does lack of DEcad abolish BCC motility (Niewiadomska et al, 1999), but also higher-than-normal expression of DEcad in rosette cells delays migration (Schober et al, 2005).…”
Section: Introductionmentioning
confidence: 99%